Radiogenic isotope studies of crust-forming processes in the Lofoten-Vesterålen province of north Norway - Wade, S; Wade, Stephen James Rochfort (1985)
﻿ The Lofoten-Vesterålen province of North Norway consists almost exclusively of Precambrian granulite-facies rocks. The oldest rocks in the province are monzonitic and dioritic migmatitic gneisses, the protoliths of which were formed at 2.7 Ga. The migmatites are overlain by a series of supracrustal gneisses, from 2.1 Ga, largely volcanogenic in origin, but with interbedded marbles and banded ironstones. The first occurrence of marble in western Lofoten is reported. Deposition in a subsiding back-arc basin or in an Andean- type environment on a thin continental margin is inferred. Both gneiss sequences were intruded by basic rocks at 1.8 Ga. The basic rocks could not have been formed simply by extraction from the mantle at 1.8 Ga. The required contribution from 2.7 Ga migmatites could be as much as 37%, but less if contamination took place via anatectic melts. The first report of eclogitic rocks from the Lofoten-Vesterålen province is made in this study; their formation is associated with shear deformation Both gneiss sequences and the basic rocks were intruded by mangeritic rocks at 1.8 - 1.7 Ga. Their chemical compositions can be explained by fractional crystallization from magmas formed from 2.7 Ga and 2.1 Ga gneisses and 1.8 Ga mantle-derived magmas. Parameters derived from Rb-Sr, Sm-Nd and U-Pb systems to express the relative proportions of crust and mantle contributions to the mangerites mutually correlate, supporting the crust-mantle source model for the mangerites. Mixing calculations suggest that the late Archaean contributes in excess of 50% by mass for almost all mangerites. Anatectic veins present, especially in the Moskenesøy supracrustal gneisses, are inferred to represent partial melts which coalesced to form the mangerites at higher structural levels. Anatexis was caused by basaltic underplating associated with limited crustal extension. Later rock-forming events were the emplacement of dolerite dykes; the 1.65 Ga Lødingen Granite; the Leknes Group metasediments and the Caledonian granite pegmatites.